The The Correlation Between Serum Vitamin D Level and Quality of Life inSystemic Sclerosis Patients - Sumartini Dewi (Indonesian Rheumatology Associantion, 2024)
Background: Systemic sclerosis (SSc) is an autoimmune rheumatic disease that is associated with disability and a reduced quality of life. Patients with SSc have lower levels of vitamin D than healthy people. Vitamin D influences the pathological mechanisms of SSc such as autoimmunity, vasculopathy, and fibrosis. The aim of this study was to know the correlation between serum vitamin D levels and the quality of life in SSc patients. Methods: This study was a cross-sectional study. Data were taken from the SSc patient registry at the Rheumatology Clinic of Dr. Hasan Sadikin General Hospital Bandung from September to November 2023. Vitamin D level were assessed by measuring serum 25-hydroxyvitamin D levels. The quality of life was measured using the Indonesian version of the Short Form (SF-36), which was divided into physical component summary (PCS) and mental component summary (MCS). Statistical analysis was performed using the Rank-Spearman test. Results: There were 81 SSc patients enrolled in this study. Vitamin D levels were found low in 44 subjects (54.3%), which were divided into 23 subjects deficiency and 21 subjects insufficiency. Thirty seven subjects (46.7%) had normal vitamin D levels. The results of this study showed that there was a significant weak positive correlation between serum vitamin D levels and PCS SF-36 (r=0.222, p=0.023) and MCS SF-36 (r=0.209, p=0.031) quality of life in SSc patients. Conclusion: Serum vitamin D levels of SSc patients had a significant weak positive correlation with physical and mental quality of life component.